Interprofessional survey on medication reconciliation activities in the US Department of Veterans’ Affairs: development and validation of an Implementation Readiness Questionnaire - Amanda Mixon; Jack Wiedrick; Blake Lesselroth; Victoria Lee Church; Kathleen Adams; Amy Richmond-Aylor; Naomi Glasscock (BMJ Open Quality, 2022)
Background Medication reconciliation (MR) can detect medication history discrepancies at interfaces-in-care and help avoid downstream adverse drug events. However, organisations have struggled to implement high-quality MR programmes. The literature has identified systems barriers, including technology capabilities and data interoperability. However, organisational culture as a root cause has been underexplored.Objectives Our objectives were to develop an implementation readiness questionnaire and measure staff attitudes towards MR across a healthcare enterprise.Methods We developed and distributed a questionnaire to 170 Veterans’ Health Affairs (VHA) sites using Research Electronic Data Capture (REDCap) software. The questionnaire contained 21 Likert-scale items that measured three constructs, such as: (1) the extent that clinicians valued MR; (2) perceptions of workflow compatibility and (3) perceptions concerning organisational climate of implementation.Results 8704 clinicians and staff responded to our questionnaire (142 of 170 VHA facilities). Most staff believed reconciling medications can improve medication safety (approximately 90% agreed it was ‘important’). However, most (approximately 90%) also expressed concerns about changes to their workflow. One-third of respondents prioritised other duties over MR and reported barriers associated with implementation climate. Only 47% of respondents agreed they had enough resources to address discrepancies when identified.Interpretation Our findings indicate that an MR readiness assessment can forecast challenges and inform development of a context-sensitive implementation bundle. Clinicians surveyed struggled with resources, technology challenges and implementation climate. A strong campaign should include clear leadership messaging, credible champions and resources to overcome technical challenges.Conclusions This manuscript provides a method to conduct a readiness assessment and highlights the importance of organisational culture in an MR campaign. The data can help assess site or network readiness for an MR change management programme.